Leveraging supply chain networks for sustainability beyond corporate boundaries: Explorative structural network analysis - Laari Sini; Wetzel Philipp; Töyli Juuso; Solakivi Tomi (Elsevier (Commercial Publisher), 2022)
The ability of companies to achieve systemic sustainability goals is influenced by the structure of the larger supply chain network in which they reside. However, managing sustainability throughout multi-tiered global supply chain networks and complying with new supply chain law initiatives has proven to be a great challenge for many firms. This article investigates node- (firm) and network-level network structural characteristics and their implications for sustainability. The empirical study first explores structural patterns in a network of 5458 companies and then focuses on a sub-set of 604 companies associated with the automotive industry. The following four sustainability archetypes were identified: impassive networks, environmentally focused networks, socially focused networks, and orchestrated networks. The article further specifies strategy options for lead firms, suppliers, and regulators in enhancing sustainability in each archetype. The most sustainable firms are typically the most central, not necessarily the ones closest to the customers. Regulators should target central firms for a ripple effect.